Multiculturalism - Watson, C. W. (Concepts in the social sciences, 2000)
The twentieth century saw an unprecedented movement of peoples from one geographical area to another. Multiculturalism is a term used to describe the variety that exists and the problems to which it gives rise. This book examines multiculturalism in the context of the national experience of countries such as France, Britain, the USA and China.